Intense Photoinduced Intervalence Charge Transfer in High-Valent Iron Mixed Phenolate/Carbene Complexes - Cadranel, Alejandro (2022)
We report high-valent iron complexes supported by N-heterocyclic carbene (NHC)-anchored, bis-phenolate pincer ligands that undergo ligand-to-metal charge transfer (LMCT) upon photoexcitation. The resulting excited states – with a lifetime in the picosecond range – feature a ligand-based, mixed-valence system and intense intervalence charge transfer bands in the near-infrared region. Upon oxidation of the complex, corresponding intervalence charge transfer absorptions are also observed in the ground state. We suggest that the spectroscopic hallmarks of such LMCT states provide useful tools to decipher excited-state decay mechanisms in high-valent NHC complexes. Our observations further indicate that NHC-anchored, bis-phenolate pincer ligands are not sufficiently strong donors to prevent the population of excited metal-centered states in high-valent iron complexes.